Initial Clinical Guidelines for Co-Occurring Autism Spectrum Disorder and Gender Dysphoria or Incongruence in Adolescents. Issue 1 (2nd January 2018) - Strang, John F.; Meagher, Haley; Kenworthy, Lauren; de Vries, Annelou L. C.; Menvielle, Edgardo; Leibowitz, Scott; Janssen, Aron; Cohen-Kettenis, Peggy; Shumer, Daniel E.; Edwards-Leeper, Laura; Pleak, Richard R.; Spack, Norman; et al.
Abstract : Evidence indicates an overrepresentation of youth with co-occurring autism spectrum disorders (ASD) and gender dysphoria (GD). The clinical assessment and treatment of adolescents with this co-occurrence is often complex, related to the developmental aspects of ASD. There are no guidelines for clinical care when ASD and GD co-occur; however, there are clinicians and researchers experienced in this co-occurrence. This study develops initial clinical consensus guidelines for the assessment and care of adolescents with co-occurring ASD and GD, from the best clinical practices of current experts in the field. Expert participants were identified through a comprehensive international search process and invited to participate in a two-stage Delphi procedure to form clinical consensus statements. The Delphi Method is a well-studied research methodology for obtaining consensus among experts to define appropriate clinical care. Of 30 potential experts identified, 22 met criteria as expert in co-occurring ASD and GD youth and participated. Textual data divided into the following data nodes: guidelines for assessment; guidelines for treatment; six primary clinical/psychosocial challenges: social functioning, medical treatments and medical safety, risk of victimization/safety, school, and transition to adulthood issues (i.e., employment and romantic relationships). With a cutoff of 75% consensus for inclusion, identified experts produced a set of initial guidelines for clinical care. Primary themes include the importance of assessment for GD in ASD, and vice versa, as well as an extended diagnostic period, often with overlap/blurring of treatment and assessment.